Crisis and rebellion in the Ottoman Empire the downfall of a Sultan in the Age of Revolution - Yildiz, Aysel (Library of Ottoman Studies, 2017)
Focusing on the uprising, and the socio-economic and political conditions which caused it, this book re-orientates Ottoman history towards Western Europe, and re-situates the late-Ottoman Empire as a key battle-ground of political ideas in the modern era.